PENGUKURAN EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK PENERANGAN JALAN TERHADAP PAJAK DAERAH KOTA BITUNG - mandagi, Jaquline imelda; Sabijono, Harijanto; Kapojos, Peter M. (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
Based on PP No. 18 of 2016 concerning Regional Apparatuses, the Bitung City Government has formed 6 agencies that will manage services to the community, one of which is the Regional Tax and Retribution Management Agency (BP2RD). The results of this study were carried out at BP2RD Bitung City, from the results of observations made, the results obtained that the Street Lighting Tax in Bitung City is a tax levied on each use of electricity, both self-generated and obtained from other sources. Based on the results of an interview with one of the employees at BP2RD, it shows that the street lighting tax revenue for the 2016 to 2020 fiscal year has increased with the achievement exceeding the target. In 2016, the Bitung City BP2RD street lighting tax revenue was Rp. 12,522,779,740, which increased to Rp. 14,931,246,641 in 2017. Then it increased again in 2018 to Rp. 18,498,678,295. In 2019, there was an increase in regional tax revenues to Rp. 19,567,645,370. In 2020 there was an increase of IDR 19,859,257,722 compared to the previous year. The analytical method used is descriptive analysis method. The results of the research on the Effectiveness of Street Lighting Tax Revenue in Bitung City for the 2016 - 2020 fiscal year are very effective with an average annual effectiveness of 117.59%. The contribution of Street Lighting Tax revenue to Bitung City's Regional Tax Revenue was quite good in 2016-2019 while in 2020 it contributed well with an average contribution of 36.07% per year.